Mimosa serra (Caesalpinioideae, Fabaceae): conservation insights and its presence in Argentina - Morales, Matías; Keller, Héctor; Fortunato, Renée H. (Phytotaxa, 2022)
In this work we detected the presence of Mimosa serra for the first time in Argentina and analyzed its distribution and status of conservation. In that country, it species is only known in one population in the Misiones province. The conservation status of the species was analyzed by means different criteria following the International Union for Conservation of Nature (IUCN) guidelines. We used the B criterion to evaluate the status of conservation at global-level and considered the B, C and D criteria to evaluate the status of conservation at country-level in Argentina. At global scale, we classified this species as Endangered (EN); it grows in few populations, some of them restricted to small and isolated swamps and grasslands in urban or agriculture areas. At country-level scale, we considered this species as Critically Endangered (CR), given its presence in only one known locality and considerable small Area of Occupancy. The method and guidelines to categorize M. serra can be extended to other species of the genus with similar ecology and distribution patterns in subtropical South America.